Machine Translation In Indian Languages - Chopra, Deepti; Joshi, Nisheeth; Mathur, Iti (International Journal of Computer Sciences and Engineering, 2025)
Machine Translation (MT) is one of the tasks of Natural Language Processing. It can be used by intellectuals to attain information from the documents written in different languages. In the following paper, we have discussed problems faced in MT in Indian languages, various approaches of MT, limitations of some of the current existing MT Systems and the work that has been done till now in MT in Indian language perspective. We have also discussed performance metrics that are used for evaluation of MT System.